Significant gender-specific difference in brain lateralization of schizophrenia patients assessed by new combined foot dominance scale - Akabalieva, Katerina (Frontiers in Psychiatry, 2023)
Objective Reduced hemispheric asymmetry has been identified as a potential risk factor for schizophrenia, characterized by diminished brain lateralization and a lack of dominance in the left hemisphere. Moreover, there is growing evidence of disrupted connectivity between various cortical regions. This study aimed to investigate gender differences in left-footedness as a potential biological marker for neuronal dysontogenesis in individuals with schizophrenia and control subjects. Materials and methods A New Combined Foot Dominance Scale (14 foot tests), comprising a Modified Chapman & Chapman Subscale (10 foot tests) and a Complex Tasks Subscale (four foot tests) was administered as performance tasks in 180 subjects [98 schizophrenia patients with mean age 34.45 years (SD = 15.67, range 23–79) for men and 42.20 years (SD = 11.38, range 21–63) for women and 82 controls with a mean age 34.70 years (SD = 16,82, range 18–79) for men and 44.50 years (SD = 10.73, range 23–67)]. As our data are not continuous and lacks normal distribution, the non-parametric Mann–Whitney test was used for comparing categorical data. Results The mean left-footedness, as assessed by the New Combined Foot Dominance Scale, is significantly higher in individuals with schizophrenia compared to control subjects. Our findings from inter-gender comparisons reveal that female schizophrenia patients exhibit a significantly greater average left-footedness than female control subjects, while in males no such a statistical significant difference is detected. Conclusion Left foot dominance is higher in patients with schizophrenia than in control subjects and women contribute significantly more to this difference.